Death Infectious: Impact of the Coronavirus Disease (COVID-19) on Stock Returns - Robin Robin (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study examines the Coronavirus disease (COVID-19) on stock returns. The independent variables are daily new deaths and daily new cases. The sample that uses in this study is financial sector, one of the most crucial sectors in an economy. Total sample is 22,930 observations during the period from March to December in 2020. This study uses unbalanced panel data and multiple regression to prove those hypotheses. The result shows that the Coronavirus disease (COVID-19) hurt on stock returns. Investors feel anxious and frightened to hear the news regarding the increasing number of deaths and the number of new cases. Investors prefer to delay investment until the capital market returns to normal. Furthermore, during the pandemic period, Friday's effect may reduce losses from stock returns. The implication of this study is that an increase in the number of deaths and the number of new cases can reduce stock returns. The government needs to suppress bad news circulating in the mass media in order to reduce investor anxiety.Â Â